Expression of a suicidal gene under control of the human secreted protein acidic and rich in cysteine (SPARC) promoter in tumor or stromal cells led to the inhibition of tumor cell growth - Lopez, María V. (2006)
The successful use of transcriptional targeting for cancer therapy depends on the activity of a given promoter inside the malignant cell. Because solid human tumors evolve as a "cross-talk" between the different cell types within the tumor, we hypothesized that targeting the entire tumor mass might have better therapeutic effect. Secreted protein acidic and rich in cysteine (SPARC) is a matricellular protein overexpressed in different human cancers malignant melanomas both in the malignant cells compartment as in the stromal one (fibroblasts and endothelial cells). We have shown that expression of the herpes simplex virus - thymidine kinase (TK) gene driven by the SPARC promoter in combination with ganciclovir inhibited human melanoma cell growth in monolayer as well as in multicellular spheroids. This inhibitory effect was observed both in homotypic spheroids composed of melanoma cells alone as well as in spheroids made of melanoma cells and stromal cells. Expression of the TK gene was also efficient to inhibit the in vivo tumor growth of established melanomas when TK was expressed either by the malignant cells. Our data suggest that the use of therapeutic genes driven by SPARC promoter could be a valuable strategy for cancer therapy aiming to target all the cellular components of the tumor mass.